Pengaruh Peran Penyuluh Pertanian Terhadap Tingkat Pendapatan Petani Kentang di Desa Rekimai Jaya Kecamatan Semende Darat Tengah Kabupaten Muara Enim - Aliyah, Aliyah; Wulandari, Siska Tri; Framita, Rabecha Maros (Universitas Batangahari Jambi, 2025)
The role of extension workers in the agricultural sector is as an advisor, technician, liaison, organizer of funds for renewal agents. The potential of agriculture and plantations in Semende Raya is very promising to be used as a center for the superior potato industry in Muara Enim with a production of 4,523.5 tons in 2022. The role of extension workers in assisting potato farmers is very much needed in order to increase potato production which can ultimately improve the welfare of potato farmers which can be seen from the increase in the standard of living and income of farmers. The objectives of the study were: 1) Analyze agricultural extension workers 2) Calculate the income of potato farmers 3) Analyze the Influence of the Role of Agricultural Extension Workers on the Income Level of Potato Farmers in Rekimai Jaya Village, Semende Darat Tengah District, Muara Enim Regency. The study was conducted in October-December 2024. The location was selected intentionally (purposively) with the consideration that in Rekimai Jaya village agricultural extension is carried out continuously and the potato agribusiness system. Based on the results of the research that has been done, it can be concluded as follows: 1) The role of extension workers with a class interval of 29-36, a frequency of 20, a percentage of 100%, the level of the role of extension workers is included in the very important category; 2) The average income is Rp. 126,675,000, - and the average income is Rp. 82,881,250, -; 3) The role of extension workers has a positive relationship with the income of potato farmers, although this relationship is relatively weak with a correlation coefficient value of R = 0.371R . The value of R2 = 0.137R ^ 2.